Water erosion on cultivated soil and soil under riparian forest - Momoli, Renata Santos; Cooper, Miguel (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to identify attributes of soil and of sediments as a tool to determine the impacts from water erosion, as well as to propose reducing the overuse of the soil in the Cerrado, in the state of Goiás, Brazil. Soils and sediments from the riparian forest of the Ponte Nova Stream and from upstream soybean crop areas were evaluated by micromorphometrics as to morphology, particle size, and porosity. Rhodic Oxisol was present in the cultivated hillside, and Petroferric Oxisol and Typic Eutraquox, in the riparian forest path. Soils and sediments were predominantly clayed, and the clay fraction was naturally aggregated into larger particles of silt and sand sizes. Analyses of morphological atributes, particle size, and porosity – by micromorphometrics – allowed to distinguish the sediment of buried soils by color, texture, and porosity differentiation. The high concentration of sandy-sized clay aggregates in Typic Eutraquox suggests the selective removal of fine particles, indicating soil erosion under the riparian forest. The high sediment deposition on the riparian forest soils is a risk to the soil filter function, and also to the perpetuity and regeneration of the forest because of the burial of seeds and seedlings.